2018
DOI: 10.1002/jcp.27070
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JNK and p38 MAPK‐mediated inflammation and apoptosis by ivabradine improves cardiac function in streptozotocin‐induced diabetic cardiomyopathy

Abstract: Inflammation plays a critical role in the development of diabetic cardiomyopathy (DCM), which has been identified as a major predisposing factor for heart failure in diabetic patients. Previous studies indicated that ivabradine (a specific agent for heart rate [HR] reduction) has anti-inflammatory properties, but its role in DCM remains unknown. This study investigated whether ivabradine exerts a therapeutic effect in DCM. C57BL/6J mice were injected intraperitoneally with streptozotocin (STZ) to induce diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…The markers of inflammation are often elevated in patients suffering from DCM, and inhibition of the inflammatory signaling pathways reduces insulin resistance and improves hyperglycemia in animal models of DM. 27,28 It has been documented that inflammation plays a critical role in the pathogenesis of DCM, which leads to cardiac fibrosis by promoting collagen deposition. In the past decade, NLRP3 inflammasome, one of the most widely studied inflammasomes, is considered a potential therapeutic target for various inflammatory diseases, including DCM.…”
Section: Discussionmentioning
confidence: 99%
“…The markers of inflammation are often elevated in patients suffering from DCM, and inhibition of the inflammatory signaling pathways reduces insulin resistance and improves hyperglycemia in animal models of DM. 27,28 It has been documented that inflammation plays a critical role in the pathogenesis of DCM, which leads to cardiac fibrosis by promoting collagen deposition. In the past decade, NLRP3 inflammasome, one of the most widely studied inflammasomes, is considered a potential therapeutic target for various inflammatory diseases, including DCM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study has revealed that the inhibition of the reactive oxygen species (ROS)-/NF-κB pathway protects cardiomyocytes from hypertrophy (10). There has been increasing evidence that inflammation and adhesion molecules are involved in diabetes and the progression of cardiac hypertrophy in diabetes (11,12). NF-κB serves an important role in the regulation of pro-inflammatory genes leading to the overproduction of inflammatory mediators, including tumor necrosis factor (TNF)-α, interleukin-6 (IL-6) and inducible nitric oxide synthase (iNOS) in the hearts of isoproterenol treated rats (13).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac dysfunction in type 1 diabetes is associated with local inflammation in the heart, including activation of stress-activated kinases JNK and p38 [56]. It is important to address the potential contribution of these kinases to coronary arteriolar vasomotor dysfunction during diabetes because p38 [46] and JNK [31] have been shown to mediate coronary arteriolar dysfunction elicited by the inflammatory molecules CRP and tumor necrosis factor-α, respectively.…”
Section: Discussionmentioning
confidence: 99%